Caenorhabditis elegans: A Simple Nematode Infection Model for Penicillium marneffei - Huang, Xiaowen; Li, Dedong; Xi, Liyan; Mylonakis, Eleftherios (PLOS ONE, 2014)
Penicillium marneffei, one of the most important thermal dimorphic fungi, is a severe threat to the life of immunocompromised patients. However, the pathogenic mechanisms of P. marneffei remain largely unknown. In this work, we developed a model host by using nematode Caenorhabditis elegans to investigate the virulence of P. marneffei. Using two P. marneffei clinical isolate strains 570 and 486, we revealed that in both liquid and solid media, the ingestion of live P. marneffei was lethal to C. elegans (P<0.001). Meanwhile, our results showed that the strain 570, which can produce red pigment, had stronger pathogenicity in C. elegans than the strain 486, which can’t produce red pigment (P<0.001). Microscopy showed the formation of red pigment and hyphae within C. elegans after incubation with P. marneffei for 4 h, which are supposed to be two contributors in nematodes killing. In addition, we used C. elegans as an in vivo model to evaluate different antifungal agents against P. marneffei, and found that antifungal agents including amphotericin B, terbinafine, fluconazole, itraconazole and voriconazole successfully prolonged the survival of nematodesinfected by P. marneffei. Overall, this alternative model host can provide us an easy tool to study the virulence of P. marneffei and screen antifungal agents.